Teaching and Learning with Research Cognitive Theory: Unlocking Curiosity and Creativity for Problem-Solving Skills - Al-Thani, Noora J; Ahmad, Zubair (SpringerBriefs in Education, 2025)
This open access volume explores the transformative role of Research Cognitive Theory (RCT) in education, emphasizing its application in fostering curiosity, creativity, innovation, problem-solving skills, and cognitive development across all educational levels in students and professional development in teachers. Through detailed discussions on integrating research-based learning with STEM education, the book offers practical insights for educators, researchers, and policymakers aiming to enhance teaching methodologies and student outcomes. By bridging the gap between theory and practice, this work serves as a vital resource for those seeking to cultivate inquiry-driven learning environments. Readers benefit from actionable strategies, case studies, and a comprehensive understanding of how RCT can revolutionize modern education.